A Fiber-Rich Dessert Made From Waste Plantain Peels: Dessert Kaya Serat Berbahan Dasar Limbah Kulit Pisang Raja - Nurjaya Nurjaya; Wery Aslinda; Ginna Mahardina (Jurnal Pengabdian Masyarakat: Svasta Harena, 2022)
Food diversification is one way to improve the nutritional quality of food in meeting food needs. Banana is one of the local plants that is easy to grow in tropical areas such as Indonesia. Banana plant is a type of plant that does not know the season that is rich in nutritional value. The banana peel ice cream product is one example of food diversification as an effort to utilize local food waste, namely banana peels where the use of banana peels is still limited. The purpose of this activity is to utilize local food waste and provide information and examples of processing banana peel waste. The results of this activity show that the nutritional content for 1 ice cream recipe contains 4897.6 kcal of energy, 64.86 grams of protein, 233.52 grams of fat, 596.6 grams of carbohydrates and 91.74 grams of fiber. In 1 recipe can be made into 30 cups of ice cream with a weight of 70 gr each. This activity can be accepted by the community, the community can also understand how to process plantain peel waste into a fiber-rich ice cream dessert. It is hoped that food waste utilization activities can be carried out in a sustainable manner so that the community can increase knowledge and understanding related to food waste.